A apropriação da leitura eletrônica por professores da Faculdade de Educação da Universidade Federal do Ceará - Freitas, Munique de Souza (2021)
The objective of this thesis was to analyze the relationship of professors at the Federal University of Ceará (UFC) with the appropriation of electronic reading. Among the specific objectives, it was intended to describe the knowledge already built on which the appropriation of electronic reading is supported; evaluate the process of mobilization of teachers for the appropriation of electronic reading and identify the meaning attributed by teachers to the appropriation of this reading. The theoretical foundation started from the concepts of Bernard Charlot's Theory of Relationship with Knowledge (2000). The notions of knowledge, mobilization, mobiles, meaning and value in the appropriation of knowledge helped to analyze the data that were collected, through a semi-structured interview, with biographical narratives being the main sources. The research subjects were nine professors, over 40, from the Faculty of Education, UFC. Teachers were literate, finished high school and entered undergraduate courses, without using TDIC in their daily lives. They got used to the resources made available by the popularization of the Internet, in the mid-1990s. In addition, the choice of subjects based on the age range considered that they had access to the Internet and to electronic reading, really, only as adults and that is why they had to take ownership of these technologies in order to use them. Three steps were taken to analyze the interviews. The first step was the creation of a general and quantitative comparison, showing points of convergence between the subjects in relation to online reading. In the second stage, the individual paths were described with the knowledge, mobiles, motives and meanings that led to the appropriation of digital technologies and online reading. In the third stage, the categories and subcategories that emerged after the analysis were presented and discussed. After this investigation, it was possible to conclude that professors, who had contact in their youth, were more interested in digital technology and were enthusiastic about the possibilities that the tools made available, appropriated more of electronic reading and digital technological resources for communication and information. Other teachers incorporated electronic reading into digital media in their daily practice, more because of the need imposed by the profession, as technology facilitates research, access to information and communication with students and with the university itself.